2018
DOI: 10.1111/ijlh.12873
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between flow cytometry and molecular findings in autosomal recessive chronic granulomatous disease: A cohort study from Oman

Abstract: Flow cytometry is a robust test of CGD diagnosis. However, results should be interpreted with caution when predicting the underlying probable genotype, and results need to be complemented with definitive molecular studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…This report confirms our previous finding that the most common form of CGD in Jordan is the AR type (21). The high frequency of AR-CGD appears also in Tunisia, Egypt, Turkey, Iran, Oman, Saudi Arabia, and Israel because of the high rate of consanguineous marriage in these countries (16,19,23,24,(48)(49)(50)(51) and it is in contrast to the published literature from USA, Europe, South America, China, and Japan, in which X-CGD is the main genetic form (4, 5,17,[25][26][27][52][53][54]. The population in Jordan amounted from 5.3 million in 2004 to 10.2 million in 2020, and is composed of a variety of ethnic groups, the majority being Arabs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This report confirms our previous finding that the most common form of CGD in Jordan is the AR type (21). The high frequency of AR-CGD appears also in Tunisia, Egypt, Turkey, Iran, Oman, Saudi Arabia, and Israel because of the high rate of consanguineous marriage in these countries (16,19,23,24,(48)(49)(50)(51) and it is in contrast to the published literature from USA, Europe, South America, China, and Japan, in which X-CGD is the main genetic form (4, 5,17,[25][26][27][52][53][54]. The population in Jordan amounted from 5.3 million in 2004 to 10.2 million in 2020, and is composed of a variety of ethnic groups, the majority being Arabs.…”
Section: Discussionsupporting
confidence: 90%
“…It is also the case in Egypt and Tunisia (23,49). However, in Israel, Saudi Arabia, Libya, Oman, Iran, and India, the AR47 0 CGD form prevails (16,24,48,51,59,64,65). However, in Turkey about 30-40% of the CGD patients have X-CGD, but AR47 0 CGD represents about 30-50% of AR-CGD too (19,75,76).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Notably, a high neutrophil SI detected using the DHR123 test does not indicate mild symptoms or a good prognosis for patients with variant type X-linked CGD. Although DHR has the advantages of requiring a small blood volume, short time, and convenience compared with direct superoxide detection, it has limitations in terms of molecular mechanism [ 64 ]. NADPH oxidase transfers electrons to molecular oxygen to generate O 2 − , which is dismutated to hydrogen peroxide (H 2 O 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, flow cytometry helps to identify the genotype-dependent variability in the evaluation of NADPH oxidase activity. It has been observed that autosomal recessive (AR-CGD) subtypes ( CYBA, NCF1, NCF2 , and NCF4 gene defects) have slightly higher amounts of residual superoxide activity compared with the X-linked recessive (XL-CGD) subtype ( CYBB gene defect) patients (48, 54). This mainly affects the severity of the clinical progression.…”
Section: Chronic Granulomatous Diseases (Cgd)mentioning
confidence: 99%